The effect of a supportive home care program on caregiver burden with stroke patients in Iran: an experimental study - Mansoureh Ashghali Farahani; Tahereh Najafi Ghezeljeh; Shima Haghani; Farshid Alazmani-Noodeh (BMC, 2021)
Abstract Background Stroke can impose a heavy burden on caregivers. Caring for stroke patients at home is more challenging than in hospitals with facilities. The purpose of this study was to evaluate the effect of a supportive home care program on caregiver burden with stroke patients. Methods This was an experimental study. One hundred sixteen caregivers of stroke patients were recruited using convenience sampling from two university-affiliated hospitals in Tehran from June 2019 to February 2020. They were randomly allocated into two groups (supportive home care program and routine hospital education program) using a randomized block design. The supportive home care program included eight educational sessions delivered in the hospital before discharge, and with home visits after hospital discharge. Caregiver burden was measured using Caregiver Burden Inventory. The data were analyzed using independent samples t-test and Analysis of Covariance. Results Caregiver burden in the routine education group increased significantly after 2 weeks, from 52.27 ± 23.95 to 62.63 ± 22.68. The mean of caregiver burden scores in the supportive home care program decreased from 44.75 ± 17.21 to 40.46 ± 17.28. The difference between the scores of the two groups before the intervention was not significantly different (t = 1.941, df = 114, p = 0.055). There was a significant difference between the two groups regarding caregiver burden scores after the intervention period (η2 = 0.305, P < 0.001). Conclusions Caregiver burden increased significantly after the discharge without proper interventions in the caregivers of stroke patients. Providing support for home care providers can help to decrease or prevent the intensification of caregiver burden.